2020
DOI: 10.3390/ijerph17186712
|View full text |Cite
|
Sign up to set email alerts
|

Associating COVID-19 Severity with Urban Factors: A Case Study of Wuhan

Abstract: Wuhan encountered a serious attack in the first round of the coronavirus disease 2019 (COVID-19) pandemic, which has resulted in a public health social impact, including public mental health. Based on the Weibo help data, we inferred the spatial distribution pattern of the epidemic situation and its impacts. Seven urban factors, i.e., urban growth, general hospital, commercial facilities, subway station, land-use mixture, aging ratio, and road density, were selected for validation with the ordinary linear mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 27 publications
(35 reference statements)
3
44
0
1
Order By: Relevance
“…Besides, in some recreation and service facilities, such as restaurants, hotels, and bars, people tend to take off their masks to talk, drink, and dine [ 38 ]. Furthermore, a large number of the commercial locations are designed as indoor spaces with inadequate ventilation, which can easily become high-risk places because the spread of the virus is intensified in confined spaces [ 41 ]. Hence, urban areas with intensive commercial facilities may be confronted with a higher virus infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in some recreation and service facilities, such as restaurants, hotels, and bars, people tend to take off their masks to talk, drink, and dine [ 38 ]. Furthermore, a large number of the commercial locations are designed as indoor spaces with inadequate ventilation, which can easily become high-risk places because the spread of the virus is intensified in confined spaces [ 41 ]. Hence, urban areas with intensive commercial facilities may be confronted with a higher virus infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Li y colaboradores encontraron que la severidad de la epidemia por SARS-CoV-2 fue mayor en las regiones estudiadas de Wuhan con mayor densidad de estaciones del metro (=0.086, p=0.004). 16…”
Section: Ecológicounclassified
“…Most of them mainly focus on the spatial distribution of different built environment factors and the epidemic situation, or only study one of the factors in depth. Li proposed and verified that six factors, including urban growth, hospital density, commercial facilities, subway stations, mixed land use and urban population aging degree were positively correlated with the severity of COVID-19 [ 29 ]. Yip’s study in the Hong Kong area found that the number of restaurants, public markets and clinics is positively related to the number of COVID-19 reported cases [ 30 ].…”
Section: Introductionmentioning
confidence: 99%